Pengaruh Struktur Kepemilikan, Masa Jabatan CEO, dan Jenis Kelamin CEO Terhadap Manajemen Laba - Nirmala, Jessica Gina; Ghofar, Abdul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the effect of family ownership, public ownership, CEO tenure, and CEO gender on the earnings management of manufacturing companies listed on the Indonesia Stock Exchange between 2019 and 2021. The samples include 243 data selected through purposive sampling method, and analyzed by multiple linear regression. The results of the study exhibit that CEO tenure has a negative effect on earnings management; family ownership, public ownership, and CEO gender have no effect on earnings management; and family ownership, public ownership, CEO tenure, and CEO gender simultaneously affect earnings management. The result of robustness test conforms with those of the initial hypothesis testing.